ANALISIS USAHATANI PADI HIBRIDA VARIETAS SEMBADA 188 DI DATARAN TINGGI SINE KABUPATEN NGAWI - Nugroho, Dhenys Bagus; Febrilyantri, Candra (JURNAL AGRIMANSION, 2024)
The productivity of rice in Indonesia needs to be improves due to the growing population. The purpose of this research is to analyze rice farming in highland areas for self-sufficiency in rice. The research method us is experimental, which aims to determine the effect of certain variables on others under controlled conditions. The result of this study show that total revenue exceeds total costs, meaning that farmers still make a profit from their farming activities. The average profit farmers earns in one harvest season is IDR 12.122.700,00. The feasibility test of rice farming in the highland of Sine Shows a ratio of 1.39. this ratio is greater than 1, indicating that rice farming with the sembada 188 variety in the highland of Sine, Ngawi regency, is financially viable.